Peri-Operative Morbidity and Outcomes of Radical Cystectomy- Institutional Experience of Single Center - Upadhyay, Amit Mani; Kunwar, Ashok Kumar; Lama, Manik; Tiwari, Kabir; Shrestha, Sanjesh Bhakta; Shah, Anil K.; Poudel, Bishnu Dutta; Amatya, Kapendra Shekhar (Nepalese Journal of Cancer, 2020)
Introduction: The incidence of urinary bladder carcinoma increases distinctly with increasing age. Radicalcystectomy has been the gold standard for the treatment of patients with muscle-invasive bladder cancer or recurrent high-grade non-muscle invasive bladder cancer. Our study aimed to see the peri-operative morbidity and surgical outcomes of the patient who had undergone radical cystectomy in our low volume center. Methods: We retrospectively reviewed the inpatient charts as well as the outpatient records of 10 patients who had undergone radical cystectomy performed in our center for 9 years. A review of the literature on perioperativemorbidity of radical cystectomy was also done using the combination of keywords like mortality, complications, and outcomes of surgery. Results: Age of the patients ranged from 40-80 years. Eight of them were male and two were female. Painlesshematuria (70%) was the commonest presenting symptom, 80% of them were smokers. Three patients received neoadjuvant chemotherapy. Nine patients had radical cystectomy with an ileal conduit, whereas one patient hadradical cystectomy with orthotropic neo-bladder. In postoperative complications, five patients had Clavien-Dindograde I, three patients had grade II, one patient had grade IIIB and one patient had grade V complications. Two years of cancer-free survival was 90% and five years of cancer-free survival was 50%. Conclusions: Radical cystectomy with ileal conduit was still the choice of surgery in muscle-invasive and recurrent high-grade non-muscle invasive bladder cancer.